The investigation of hydrogenation influence on structure changes of zirconium with nickel layer - Kudiyarov V. N. Victor Nikolaevich; Bordulev Yu. S. Yuri Sergeevich; Laptev R. S. Roman Sergeevich; Pushilina N. S. Natalia Sergeevna; Kashkarov E. B. Egor Borisovich; Syrtanov M. S. Maksim Sergeevich (2016, 2016)
Title screen